Decision making from the perspective of nursing students - Marques,Maria de Fátima Mendes (2019)
ABSTRACT Objective: To analyze the decision making of students from a nursing higher school and understand how they make decisions in the care process. Method: A qualitative study with an exploratory and descriptive approach was carried out with the case study method. Results: Six types of decision making were categorized by the students as follows: Decision about communication (15 record units [RU]); Decision about understanding (14 RU); Decision about intervention (9 RU); Decision about timing (5 RU); Decision about targeting (4 RU); and Decision about management (0 RU), with a total of 47 RU. Final considerations: Analysis of the learning diaries showed that students make more decisions regarding communication with patients and understanding of the care situation, than with the acting decision.